ELLE, VOGUE, BAZAAR: STUDI KARAKTERISTIK TIPOGRAFI PADA MEREK DI SAMPUL MAJALAH FESYEN BULAN JANUARI SAMPAI APRIL 2019 - Sari, Ni Luh Pangestu Widya; Agetania, Ni Luh Putu (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2019)
Many famous fashion magazines entrust the identity and characteristics of their products to the typography used as the logotype (word mark) of a company or magazine brand. Each type of letter carries its own character which then builds the character of the product they have been created. The character of a letter also influences people's perception of the products presented in this fashion. BAZAAR, ELLE, and VOGUE were chosen as representatives of fashion magazines around the world, given their very long appearance (starting in 1867) and the history of their emergence during the industrial revolution and are still popular today. This study aims to determine the impression obtained from typographic characteristics in the fashion magazine brand BAZAAR, ELLE, and VOGUE.